RNA‐sequencing analysis reveals the potential molecular mechanism of RAD54B in the proliferation of inflamed human dental pulp cells. (13th October 2022) - Huang, Pei; Wang, Fushi; Wang, Xinhuan; Meng, Xiujiao; Qiao, Weiwei; Meng, Liuyan
Abstract: Aim: To investigate the role of RAD54B in the proliferation of inflamed human dental pulp cells (hDPCs) induced by lipopolysaccharide (LPS). Methodology: Normal, carious and pulpitic human dental pulp tissues were collected. Total RNA was subjected to RNA‐sequencing (seq) and gene expression profiles were studied by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Differentially expressed genes (DEGs) in homologous recombination repair (HRR) were validated with qRT‐PCR. The expression of RAD54B and TNF‐α in human dental pulp tissues was detected using immunohistochemistry. HDPCs were cultured and RAD54B level in hDPCs was detected after LPS stimulation using western blot. CCK‐8 was used to investigate the proliferation of hDPCs transfected with negative control (Nc) small interfering RNA (siRNA), RAD54B siRNA, P53 siRNA or both siRNAs with or without LPS stimulation. Flow cytometry was used to detect the cell cycle distribution, and western blot and immunofluorescence were used to analyse the expression of RAD54B, P53 and P21 under the above treatments. One‐way and two‐way anova followed by least significant difference posttest were used for statistical analysis. Results: RNA‐seq results identified DEGs amongst the three groups. KEGG pathway analysis revealed enrichment of DEGs in the replication and repair pathway. HRR and non‐homologous end joining (NHEJ) components were further verified and qRT‐PCR results were basically consistent with the sequencing data. RAD54B, an HRR accessory factor highly expressed in carious and pulpitic tissues as compared to that in normal pulps, was chosen as our gene of interest. High RAD54B expression was confirmed in inflamed human dental pulp tissues and LPS‐stimulated hDPCs. Upon RAD54B knockdown, P53 and P21 expressions in hDPCs were upregulated whereas the proliferation was significantly downregulated, accompanied by increased G2/M phase arrest. After inhibiting P53 expression in RAD54B‐knockdown hDPCs, P21 expression and cell proliferation were reversed. Conclusions: Gene expression profiles of normal, carious and pulpitic human dental pulp tissues were revealed. HRR components were elucidated to function in dental pulp inflammation. Amongst the DEGs in HRR, RAD54B regulated the proliferation of inflamed hDPCs via P53/P21 signalling. This research deepens our understanding of dental pulp inflammation and provides new insight to clarify the underlying mechanisms.